The Effect of BAP and Kinetin Concentrations for shoot induction on Teak (Tectona grandis L.) with In Vitro method - Prameswari, Mayang Arnindika; Karno, Karno; Anwar, Syaiful (Journal of Tropical Crop Science and Technology, 2019)
The purpose of this research was to examine interaction effect between the different concentration of BAP hormone (Benzylaminopurine) and Kinetin hormone on the shoot induction of Jati (Tectona grandis L.) with in vitro method. This research used a completely randomized factorial design with 4x3 factorial pattern. The first factor was the concentration of BAP (B0 = 0 ppm; B1 = 1 ppm; B2 = 2 ppm dan B3 = 3 ppm). The second factor was concentration of Kinetin (K0 = 0 ppm; K2 = 0,75 ppm; dan K3 = 1,5 ppm). The parameters observed were time of callus appearance, callus length, time of shoot emergance, number of shoots, length of shoots, time of leaf development, number of leaves, percentage of growth, and percentage of contamination. The parameters obtained were analysed descriptively because the percentage of total growth was under 50%. The result showed that the concentration 1 ppm BAP and 0,75 ppm kinetin was better for stimulating the appearance of callus, shoots, leaves, and number of shoots. Callus diameter was better at concentration of BAP 3 ppm. The callus texture that was formed was included in the compact texture. The percentage of explants life was 33,30 – 66,60%. No contamination occurred in all explant samples.